Gloss to the judgement of the Supreme Court of 14 December 2017, II PK 322/16 - Piątkowski, Jan; Rutkowska, Beata (Studia Iuridica Toruniensia, 2020)
The subject matter of the judgement are the issues concerning the violation of the principle of equal treatment in employment. While the Supreme Court has convincingly proved that it is not the violation of the said principle if the differences in remuneration of given employees result from their performance of diverse jobs – both in the objective context (qualifications and professional experience) and the subjective one (level of liability and effort), the doubts are caused by the thesis expressed as part of consideration concerning a failure of an employer to grant interim leaves of a trade union nature. The Supreme Court has decided that a failure to grant paid leave to an employee so that they could participate in a few-day trade union training does not constitute a violation of Article 31, section 3 of the Act on trade union organizations, nor it is a form of discrimination of the employee, since the interim leave from work refers to short-term, sudden activities justified by a crucial need of a trade union nature. This view stems from the content of Article 80 of the Labour Code. The basis for stating the meaning of a term “interim activity resulting from a trade union function” should not be Article 80 of the Labour Code which in fact regulates a different matter, i.e. remuneration for work, but a regulation provided for in the Act on trade union organizations, which refers directly to this institution.